A comparative study of formulaic expressions in the interlanguage (Filipino English) of Filipino bilinguals in Philippine and American settings the influence of social and psychological distance - Gonzales, Mildred J.
This study aimed at describing the process of second language acquisition (SLA) relative to the process of de-stabilization of native varieties of English. Taking off from Tan's research in existing Filipino english formulaic expressions in the repertoire of Filipino graduate students, the study investigated social and psychological variable as well as attitudes/motivations which influenced the persistence or de-stabilization of Filipino English formulas expressions in the speech of 64 filipinos bilingual immigrants in the American setting. It also determined the comprehensibility and acceptability of frequently used Filipinos formulaic expressions. Specifically the study centered on the following : 1 ) forms of formulaic expressions produced by Filipino bilingual immigrants in the American setting; ( 2 ) the social and personality characteristics of the immigrants who acquire the American English norm vis-à-vis those who persist in the use of Filipino English or use other forms; and ( 3 ) the comprehensibility and acceptability of these formulaic expressions. The formulaic expressions were elicited through the spontaneous written responses of the subjects to a 30-item test. Measure of socio-psychosocial distance and attitudes/motivations were administered to find out the subjects' social and personality characteristics that facilitate de-stabilization or contribute to fossilization of their existing Filipino english formulaic expressions. Four groups of judges consisting of Filipino and American professionals rated the comprehensibility and acceptability levels of frequently used Filipino English formulaic expressions presented in context using two 5-point scale instruments. Statistical tools used in the study were percentages, means, Z value for two independent proportions chi-square (X2) test of independence, t-test of significance of difference between means, Pearson product-moment correlation formula, step-wise multiple regression, and analysis of variance (ANOVA). The findings of the study are summarized as follows: (1) The deviant forms of formulaic expressions in English produced by the Filipino bilingual immigrants in the American setting were: a) 1056 America English formulaic expressions; b) 71 Filipino English formulaic expressions which correspond to Tan's; c) 389 frequently used deviant formulaic expressions produced only in the American setting; and d) 424 other deviant forms not frequently used. Filipino English formulaic expressions existing in the repertoire of Filipino bilingual immigrants de-stabilize at a rapid rate. Teenage subjects produced more varieties of Filipino English formulaic expressions. The social and personality characteristics of the Filipino bilingual immigrants who acquired the American English norms differed from those Filipino bilingual immigrants who persisted in the use of Filipino English formulaic expressions as indicated by measures of socio-psychological distance and attitudes/motivations. The following factors, all reflecting low enclosure, influenced the de-stabilization of Filipino English formulaic expressions: 1. rejection of the following traits in the FILIPINO BILINGUAL IMMIGRANT by the subjects: unhappy, socially awkward, not confident, secretive (hypo-critical), and dim future. 2. acceptance of the following traits in the AMERICAN NATIVE SPEAKER by the subjects : happy, socially graceful, confident, open (frank), and bright future; 3. avoidance of national identity indices as eating Filipino food, wearing native costumes, preparing a party with Filipino dishes by the Filipino bilingual immigrant; 4. avoidance of interaction situation indices by the Filipino bilingual immigrant as interacting with Filipinos, attending a Filipino party, going out on picnics withFilipinos, visiting a Filipino family on weekends, and calling up Filipinos by phone. 5. choice of Asians and black Americans, or non-native and native speakers of L2, rather than Filipinos, as reference groups.On the other hand, these factors, all reflecting high enclosure, influenced the fossilization of Filipino English formulaic expressions : 1. rejection of the following traits in the AMERICAN NATIVE SPEAKER by the subjects: not capable, stupid, uneducated, dependent, and unreliable; 2. rating Filipinos the highest as friends/associates; 3. age of arrival beyond the sensitive and critical periods, with the LOR of the teenage group fossilizing, while that of the professional group de-stabilizing, the Filipino English formulaic expressions. On the basis of the foregoing findings, some implications for language teaching and research are considered. Recommendations concerning possible changes in teacher behaviour, methodology, content, and materials of language teaching are forwarded.